2021
DOI: 10.1007/s40119-021-00224-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Effect on Renal Parameters of Amlodipine vs. Other Dihydropyridine Calcium Channel Blockers in Patients with Essential Hypertension: Retrospective Observational Study Based on Real-World Evidence from Electronic Medical Records

Abstract: Introduction: The renoprotective effects of dihydropyridine calcium channel blockers (CCBs) have been established as non-inferior to other classes of antihypertensive drugs. Studying their effect on renal outcome parameters, specifically for amlodipine as monotherapy, in real-world settings can further help in expanding its usage among Indian patients. This study was performed to assess the effects of amlodipine and other dihydropyridine CCBs (cilnidipine, benidipine and azelnidipine) on renal parameters and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our pooled analysis also shows that cilnidipine does not significantly change serum creatinine levels as well as GFR. But this study provides evidence that cilnidipine has renal protective actions as it significantly decreases proteinuria in CKD patients, which supports the previous meta-analysis in which renal function was assessed among hypertensive patients receiving cilnidipine and L-type CCBs and cilnidipine showed better improvement in urinary protein excretion with similar effect on serum creatinine [16]. It can be explained by N-channel blocking the action of cilnidipine.…”
Section: Discussionsupporting
confidence: 88%
“…Our pooled analysis also shows that cilnidipine does not significantly change serum creatinine levels as well as GFR. But this study provides evidence that cilnidipine has renal protective actions as it significantly decreases proteinuria in CKD patients, which supports the previous meta-analysis in which renal function was assessed among hypertensive patients receiving cilnidipine and L-type CCBs and cilnidipine showed better improvement in urinary protein excretion with similar effect on serum creatinine [16]. It can be explained by N-channel blocking the action of cilnidipine.…”
Section: Discussionsupporting
confidence: 88%
“…Azelnidipine has no obvious toxic side effects in the clinical treatment of hypertension. 48 Therefore, azelnidipine is a valuable FDA-approved drug targeting MEK1/2 in the chemoprevention of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding percentage of patients in cilnidipine group was 14.5%. Jadhav et al (2021), in an EMR-based study, comparing amlodipine with other CCBs, on Indian population observed amlodipine as the preferred drug of choice with long-lasting effectiveness and greater effect at lower doses [ 27 ]. Amlodipine with longer half-life ( t 1/2 = 30–60 hours) than cilnidipine half-life ( t 1/2 = 2.5 hours), high bioavailability, and affordability has an added advantage as antihypertensive for Indian population.…”
Section: Discussionmentioning
confidence: 99%